Three second chromosome-linked clustered Cyp6 genes show differential constitutive and barbital-induced expression in DDT-resistant and susceptible strains of Drosophila melanogaster. - Maitra, S.; Dombrowski, S.M.; Waters, L.C.; Ganguly, R. (Gene, 1996)
The level of expression of the Cyp6a2 gene is much higher in the DDT-resistant 91-R strain than in the susceptible 91-C strain of Drosophila melanogaster (Waters et al. (1992b) Proc. Natl. Acad. Sci. USA, 89, 4855-4859). To understand the role of Cyp6a2 and related genes in insecticide resistance, we have isolated and characterized two new Cyp6 genes from the 91-R strain. The polypeptides encoded by these two genes, Cyp6a8 and Cyp6a9, show 77 and 75% amino acid sequence similarity, and 60 and 55% identity with Cyp6a2 of D. melanogaster, respectively. In the genome, Cyp6a8 and Cyp6a9 genes are closely clustered within 4 kb and map at region 51C of the second chromosome. In between them another Cyp gene is present which is more related to Cyp6a9 than to Cyp6a8. The Cyp6a8 gene which is transcriptionally highly active in 91-R, moderately active in ry506 and silent in the 91-C strain hybridizes with 2.0- and 1.8-kb RNAs. Two different-sized RNAs, 2.1 and 1.8 kb, also hybridize with the Cyp6a9 and/or Cyp6a9-related genes. While the level of 2.1-kb RNA is similar in all three strains, the level of 1.8-kb RNA is highest in the 91-R strain and barely detectable in 91-C strain. Transgenic experiments showed that a 8.3-kb BamHI fragment contains the cis-regulatory elements for the expression of both Cyp6a8 and Cyp6a9-related genes. Barbital induces all these genes in all three strains and increases the levels of the two Cyp6a8 transcripts and the 1.8-kb RNA produced by the Cyp6a9 and/or Cyp6a9-related genes. Expression of the Cyp6a8 gene is down-regulated in the hybrids of 91-R and 91-C strains despite the fact that the hybrids carry one copy of the highly active allele of the Cyp6a8 gene of the 91-R strain. Based on these results we propose that the Cyp6a8 gene in 91-C strain may be turned off by an active repressor which might be inhibited by barbital treatment. In the 91-R strain, the putative repressor may be defective, allowing high level of constitutive expression of the Cyp6a8 gene.